Problema logístico de transporte para la elaboración de rutas médicas domiciliarias de la Clínica Nueva Rafael Uribe Uribe en la ciudad de Santiago de Cali (2021)
The following proposal aims to design a proposal to optimize the route of the home medical routes of the new Rafael Uribe Uribe clinic in the city of Santiago de Cali, adjusting to the VRP vehicle routing problem, using the Nearest Neighbor Heuristic to structure the problem. The problem became operational based on a methodological design that is based on three (3) aspects that give sustainability to the research: A quantitative approach with qualitative and explanatory aspects that allow identifying the causes that produce routing problems in home care at the new Rafael Uribe Uribe clinic. To achieve a balanced development of the proposal, two solution systems are proposed to determine the critical path, that is, the one that has the shortest distance, uses the shortest travel time and therefore has the lowest cost. The objectives of the project, such as: The nearest neighbor heuristic and the solver programming tool in order to find the least cost route and in turn define the number of vehicles to use